External ocular findings in lupus erythematosus: a clinical and immunopathological study. Issue 3 (March 1990) - Frith, P; Burge, S M; Millard, P R; Wojnarowska, F
Abstract : A selected group of 18 patients with systemic lupus erythematosus (SLE) and 30 patients with chronic cutaneous lupus erythematosus (CCLE) showed an unexpectedly high incidence of problems involving the globe or eyelids. Five SLE patients had recurrent episcleritis, two CCLE patients had lower tarsal plaques, and two further CCLE patients had erosion of the lower lid margins associated with conjunctival scarring and symblepharon. This association has not previously been reported. There was an unexpectedly high incidence of deposition of immunoreactants in a linear pattern at the basement membrane zone in normal bulbar conjunctiva, which occurred in both SLE (42%) and CCLE (50%). The significance of these findings is discussed. We believe surface ocular problems in lupus erythematosus to be under-reported and that direct immunofluorescence of bulbar conjunctival biopsy might be helpful in diagnosis.